Caracterização estrutural e propriedades mecânicas e tribológicas de ferro fundido branco alto cromo com adição de nióbio - Dimas de Andrade Pacheco (2018)
Abrasive wear is one of the most common industrial problems, especially in mining. The abrasive wear mechanism depends strongly on material properties (hardness and toughness) as well as on the tribosystem (hardness and shape of the abrasive, associated stress and abrasive constraint). High chrome white cast iron is a widely-used material for high abrasive wear protection due to its high hardness of chromium carbides. The addition of 2.35% of niobium in a high chromium cast iron containing 25.6% Cr, 2.9% C and 1,0% Mo changed its microstructure. Initially eutectic, it became hypoeutectic. A 32% carbide volume fraction reduction was observed for eutectic (Fe,Cr)7C3 after niobium addition. The niobium carbide precipitation in compact and non-compact form was the main cause. The addition resulted in a bulk hardness decrease, a retained austenite almost free structure after heat treatment and a martensitic matrix with higher indentation hardness when compared to the alloy without Nb. The wear mechanism in the bottom part of iron ore transfer chutes is very similar to dry sand rubber-wheel abrasion test, mainly ploughing. Dry sand rubber-wheel abrasion results did not show a statistically significant difference for high severity condition (130N force against specimen). However, the alloy with niobium addition showed 15,6% wear rate decrease when submitted to low severity condition (45N). The decrease in test severity indicated a change in wear behavior for the alloy containing niobium. A preferential wear of the matrix occurs in both conditions, followed by carbide fracture or grain pull-out. For 45N, the wear rate is mainly controlled by the wear rate of the matrix. In this condition, the matrix hardness is a key factor. In more severe conditions, matrix degree of protection becomes the main factor for the wear resistance